Determinan stunting pada anak usia di bawah lima tahun di Aceh: Analisis data SUSENAS dan SSGBI 2019 - Kobat, Reny Ivaqueene; Ahmad, Aripin; Zahara, Meutia (Jurnal SAGO Gizi dan Kesehatan, 2025)
Background: Stunting in children under five years of age is a chronic nutritional problem that has long-term impacts on the quality of physical growth and cognitive development of children. Aceh has recorded a high prevalence of stunting (SSGBI 2019:34,18%); however, studies that integrate national data to identify actionable local determinants remain limited.Objective: To identify factors associated with stunting among children under five years of age in Aceh and determine the dominant factors that could become the focus of local policy interventions.Methods: This cross-sectional study analyzed secondary data from the 2019 Susenas and SSGBI. The sample was selected as a subset of all households in Aceh Province that were recorded in both surveys and met the inclusion criteria (children aged 0–59 months with complete anthropometric and related variable data), resulting in 1,019 children in 2019. Multistage stratified cluster sampling was conducted by the BPS and Ministry of Health. Stratified data from Aceh Province were used for this analysis. The analysis included descriptive analysis, bivariate tests (chi-square), and multivariate logistic regression to identify determinant factors (Adjusted Odds Ratio [AOR], 95% confidence level).Results: The prevalence of stunting among children under five years of age in Aceh was 27,67% (n=1,019). In the bivariate analysis, factors significantly associated with stunting were Early Initiation of Breastfeeding (EIBF) (p=0,002), exclusive breastfeeding (p=0,043), access to food (p=0,033), access to information media (p=0,001), parental education (p<0,05), birth spacing (p=0,000), and area (urban/rural) (p=0,003). In the multivariate model, the dominant factors increasing the odds of stunting were severe household food insecurity (AOR=1,56), not accessing health information media (AOR=1,51), living in rural areas (AOR=1.40), and not practicing EIBF (AOR=1,40), all of which were significant at p<0,05.Conclusion: Food security is the most dominant factor associated with stunting in Aceh, Indonesia. Recommended interventions include strengthening family- and community-based food security programs (including targeted food assistance and food diversification), improving maternal nutrition education during the first 1,000 days of life with empowerment strategies through accessible information media, and enhancing breastfeeding support and posyandu services in rural areas.